Evolutionary history of the complex polymorphic dobsonfly genus Neoneuromus (Megaloptera: Corydalidae). (5th June 2018) - YANG, FAN; CHANG, WENCHENG; HAYASHI, FUMIO; GILLUNG, JESSICA; JIANG, YUNLAN; YANG, DING; LIU, XINGYUE
Abstract: The dobsonfly genus Neoneuromus van der Weele is endemic to the Oriental region. Species possess highly variable body and wing colouration and markings, not only among species but also among conspecific individuals of certain species. This stark polymorphism hinders accurate species identification, and obscures an undocumented species diversity as well as our understanding of the evolutionary history of this genus. We used multiple methods of molecular identification combined with morphological evidence to delimitate species, circumscribing a total of 13 species in Neoneuromus . Five new species are herein described: Neoneuromus indistinctus Liu, Hayashi & Yang, sp.n., Neoneuromus maculatus Liu, Hayashi & Yang, sp.n., Neoneuromus niger Liu, Hayashi & Yang, sp.n., Neoneuromus similis Liu, Hayashi & Yang, sp.n. and Neoneuromus vanderweelei Liu, Hayashi & Yang, sp.n. The dated phylogeny with reconstructed ancestral areas indicates an initial divergence of Neoneuromus during the mid‐Eocene. A broad area including northeastern India and northern Indochina could be a centre for early divergence of the genus, while complex dispersal and vicariance events dating from the late Eocene to the Pliocene probably shaped the present diversity and distribution of the genus. Our ancestral character state reconstruction suggests that the pale and dark colour forms among different species, or conspecifics, could evolve rapidly and that changes in colouration could be driven by species‐specific mate recognition. Abstract : We identified 13 species of dobsonfly genus Neoneuromus using combined approaches with molecular and morphological evidence, and five new species are herein described. The initial divergence of Neoneuromus probably occurred around northeastern India and northern Indochina during the mid‐Eocene, followed by complex dispersal and vicariance events that shaped the present distribution. The pale and dark colour forms among different species or conspecific individuals in Neoneuromus could be rapidly evolved from one another.